2019
DOI: 10.1371/journal.pcbi.1007089
|View full text |Cite
|
Sign up to set email alerts
|

Evidence accumulation is biased by motivation: A computational account

Abstract: To make good judgments people gather information. An important problem an agent needs to solve is when to continue sampling data and when to stop gathering evidence. We examine whether and how the desire to hold a certain belief influences the amount of information participants require to form that belief. Participants completed a sequential sampling task in which they were incentivized to accurately judge whether they were in a desirable state, which was associated with greater rewards than losses, or an unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 42 publications
7
41
0
Order By: Relevance
“…This prediction might be somewhat counterintuitive, as the motivation for information seeking is expected to be higher when the current evidence favors the less desirable state (the low-reward jar). However, it is consistent with the widespread notion of confirmation bias that an agent needs less evidence to bet on a desirable state than an undesirable state (e.g., Gesiarz et al, 2019). More generally, the prediction echoes the general assumption that information seeking should be driven not by the motivation to predict the state (which jar is the true jar?)…”
Section: Theorysupporting
confidence: 78%
See 1 more Smart Citation
“…This prediction might be somewhat counterintuitive, as the motivation for information seeking is expected to be higher when the current evidence favors the less desirable state (the low-reward jar). However, it is consistent with the widespread notion of confirmation bias that an agent needs less evidence to bet on a desirable state than an undesirable state (e.g., Gesiarz et al, 2019). More generally, the prediction echoes the general assumption that information seeking should be driven not by the motivation to predict the state (which jar is the true jar?)…”
Section: Theorysupporting
confidence: 78%
“…Our theoretical and behavioral findings may provide some insight into confirmation biases observed across domains. Confirmation bias is commonly framed as biases in updating processes and/or decision criteria due to reward asymmetry or other factors such as pre-commitment (Gesiarz et al, 2019; Leong et al, 2019; Luu & Stocker, 2018; Talluri et al, 2018). We showed that, even without biases in updating or decision criteria, information seeking should be biased by reward asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…This research indicates that people prefer to seek information that confirms their beliefs and has positive valence, as when we read an additional news story about the victory of a favored political party. This type of motivated search is evident both in laboratory experiments ( 9 11 ) and in real-world data ( 12 14 ).…”
mentioning
confidence: 92%
“…In recent years, cognitive neuroscience has started to reveal the mechanisms underlying information gathering and how healthy adults solve this challenge. A key finding is that humans dynamically adjust their decision criteria depending on how long they have been sampling, and not necessarily based on explicit objective sampling costs ( Bogacz, Wagenmakers, Forstmann, & Nieuwenhuis, 2010 ; Gesiarz, Cahill, & Sharot, 2019 ; Hauser, Moutoussis, Iannaccone, et al, 2017 ; Ma, Sanfey, & Ma, 2019 ; Malhotra, Leslie, Ludwig, & Bogacz, 2017 ; Thura, Cos, Trung, & Cisek, 2014 ). This behaviour is evidence for subjective sampling costs that increase as more information is gathered, rendering a long information sampling process unattractive.…”
Section: Introductionmentioning
confidence: 99%